Overshadowed by kala - Michał Lubina (Ksiegarnia Akademicka Publishing, 2021)
India seems to fit well with Burma. Long common history, deep cultural relations, similar heritage and geographic proximity – all this should help to upgrade India‑Burma relations. There is, however, one major obstacle: a historical and cultural burden, which can be summarized by the Burmese name for Indians: kala. Literally kala means “alien,” but at present it refers to Indians only. In Burmese conditions it has a wider, metaphorical meaning: something between “unwanted,” “hated” and “despicable.” In this sense, kala is a cultural phenomenon, a kind of “burdensome heritage” that influences the political relations between India and Burma. In this way, kala still looms large on the horizon of India‑Burma relations blocks their development.